2001
DOI: 10.1093/jn/131.9.2429s
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Healthy Functioning in the Developing World

Abstract: There is a general lack of data for studying the relationship between nutrition and healthy functioning among the elderly in developing countries. Nevertheless, knowledge of biological relationships from studies in other countries can be applied to gain an understanding of what can be expected in the developing world. In this respect, the concept of the nutrition transition is important. However, nutrition transition as related to elderly populations in developing countries has not yet been adequately studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Mobility is affected significantly positively for men and the confidence regions for the 60-69 and 70-79 suggest that there may be a positive effect overall in both cohorts. In countries such as China (Zohoori, 2001) and Turkey (Bahat et al, 2012) the likelihood of an inability to perform any IADLs has been found to be negatively associated with BMIs. Such association could play a role here as well.…”
Section: Resultsmentioning
confidence: 99%
“…Mobility is affected significantly positively for men and the confidence regions for the 60-69 and 70-79 suggest that there may be a positive effect overall in both cohorts. In countries such as China (Zohoori, 2001) and Turkey (Bahat et al, 2012) the likelihood of an inability to perform any IADLs has been found to be negatively associated with BMIs. Such association could play a role here as well.…”
Section: Resultsmentioning
confidence: 99%
“…Poor diet is one of the factors linked to chronic diseases [10]. Persons with impaired function may have difficulties in carrying out activities of everyday life [11].…”
Section: Introductionmentioning
confidence: 99%
“…Availability of money to purchase food is perhaps the most important factor affecting food intake in many retired elderly. [30][31][32][33][34] The self perceived adequacy of income to purchase nutritious food was associated with nutritional status of the elderly in this study. The increase in medical illnesses among the elderly, bring with it the need for prescription medications.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs represent a significant expense for elderly and its purchase, may limit the amount of money available for food. 1,6,14,15,22,[31][32][33] Activity level was associated with the nutritional status of the subjects. Restricted mobility because of arthritis, shakiness or lack of coordination as a result of neurodegenerative changes can make food preparation, eating and/or cleaning up rather difficult tasks.…”
Section: Discussionmentioning
confidence: 99%